The Dark Side of Play: How FOMO and Anticipated Gaming Enjoyment Drive Impulsive Buying and Brand Addiction in Roblox - Ardyan, Elia; Al Mubarak, Mahesha (Universitas Muhammadiyah Yogyakarta, 2026)
This study applies the Stimulus-Organism-Response (SOR) framework to examine the negative consequences of digital gaming consumption driven by emotional and social stimuli in a social gaming environment. The research aims to investigate how anticipated gaming enjoyment and fear of missing out (FOMO) influence impulsive buying behavior and its subsequent effects on brand resonance and brand addiction. Data were collected from 216 active Roblox players and analyzed using SEM-PLS. The findings reveal that both anticipated enjoyment and FOMO significantly stimulate impulsive buying. Furthermore, impulsive buying positively affects brand resonance, which in turn leads to brand addiction, indicating a psychological consumption continuum. The results suggest that emotionally driven episodic purchases can evolve into compulsive and emotionally attached consumption behaviors toward brands. This study contributes to the SOR literature by empirically confirming the causal chain from emotional stimuli to maladaptive consumption outcomes, highlighting brand addiction as a critical consequence often overlooked in prior research. The implications emphasize the need for ethical game design, transparent monetization strategies, and regulation of FOMO-driven features. Additionally, the study provides practical insights for digital marketers and game developers while underscoring the importance of maintaining a balanced level of gaming engagement for users’ psychological well-being.